Both a visual and a semiquantitative analysis for differentiating benign from malignant chondrogenic bone tumors using Tc-99m (V) DMSA scintigraphy: a prospective study. Issue 8 (August 2015) - Shinya, Takayoshi; Sato, Shuhei; Kunisada, Toshiyuki; Inai, Ryota; Yanai, Hiroyuki; Ozaki, Toshifumi; Kanazawa, Susumu
Abstract : Objective: The aims of this prospective study were to assess the relationship between tumor aggressiveness and Tc-99m (V) dimercaptosuccinic acid (DMSA) uptake in chondrogenic bone tumors and the value of Tc-99m (V) DMSA scintigraphy for differentiating benign from malignant tumors. Methods: Twenty-four patients with chondrogenic tumors (19 benign and five malignant) underwent Tc-99m DMSA (V) scintigraphy. Radiopharmaceutical uptake was classified using a three-point scale to allow a visual-only analysis, and a tumor-to-background contrast (TBC) was computed using regions of interest to provide a semiquantitative analysis. Spearman's correlation coefficient was used to assess the correlation between tumor aggressiveness and TBC. The difference in TBC between benign and malignant tumors was analyzed with the Mann–Whitney U -test. An appropriate cutoff value of TBC was chosen for the diagnosis of malignancy of a tumor using receiver operating characteristic analysis. Results: Six benign tumors showed negative uptake (uptake score 0), whereas 13 benign tumors showed positive uptake ( n =10 uptake score 1; n =3 uptake score 2). All chondrosarcomas showed positive uptake ( n =2 uptake score 1; n =3 uptake score 2). A significant correlation was found between tumor aggressiveness and TBC. A significant difference was seen in TBC between benign and malignant tumors. With the chosen cutoff value of TBC equal to 0.611, the sensitivity was 80.0%, specificity was 78.9%, the positive predictive value was 50.0%, and the negative predictive value was 93.8%. Conclusion: Tc-99m (V) DMSA scintigraphy may have the potential to improve diagnostic methods for detecting chondrosarcomas using visual and/or semiquantitative analyses.